PALS1-dependent modulations of mRNA profiles in MDCK II cells grown in non-confluent monolayers and three-dimensional cysts - Klaus Schughart; Annika Möller-Kerutt; Verena Höffken; Pavel Nedvetsky; Ann-Christin Groh; Daniela Anne Braun; Hermann Pavenstädt; Thomas Weide (BMC Genomic Data)
Abstract In epithelia, apicobasal cell polarization is closely linked to cell-cell contact formation, both controlled by the conserved Crumbs (CRB) complex, which includes the transmembrane protein Crumbs (CRB3a) and adapter proteins PALS1, PATJ, and LIN7c. In MDCK II cells, a model for cell polarization, depletion of PALS1 - which binds to all CRB components - leads to defective cell polarization and improper distribution of tight junction proteins, resulting in severe epithelial barrier defects in 3D cyst models. This study investigated whether this phenotype is associated with transcriptional changes by analyzing wildtype (WT) and PALS1 knockout (KO) MDCK II cell lines grown under non-confluent conditions and in 3D cyst cultures. Our results indicate that the transition from non-confluent cells to 3D cysts involves numerous differentially expressed genes (DEGs) in both WT and KO cells. Importantly, the analyses revealed significant overlaps between WT and KO cells in their maturation processes, suggesting that most identified DEGs are linked to differentiation from non-confluent to polarized MDCK cells and likely not a result of PALS1 deficiency. Gene Ontology (GO) enrichment and over-representation analyses using REACTOME and KEGG databases confirmed these similarities. In contrast, the direct comparison of WT and KO cells at the two stages showed fewer DEGs and overlaps in associated biological processes and signaling pathways. DEGs associated with the 3D stage, in which the phenotype manifests, contain DEGs and pathways that were predominantly linked to cell cycle linked processes, centromere assembly, or DNA replication. Furthermore, the transcription of genes encoding key junction proteins, additional polarity proteins, and cell-substrate interaction proteins is less affected by the loss of PALS1, indicating that PALS1 influences the transcriptional profiles in epithelial cells as a modulating factor.